Improved performance of quantitative collagen parameters versus standard histology in longitudinal assessment of nonadvanced liver fibrosis for chronic hepatitis B. Issue 5 (27th December 2017) - Wang, Y.; Liang, X.; Yang, J.; Wang, H.; Tan, D.; Chen, S.; Cheng, J.; Chen, Y.; Sun, J.; Rong, F.; Yang, W.; Liu, H.; et al.
Summary: Monitoring longitudinal nonadvanced fibrosis is a more common scenario in management of chronic hepatitis B (CHB), for which, however, current evaluation methods generally lack sufficient performance. We conducted a proof‐of‐concept study to evaluate the performance of quantitative fibrous collagen parameters (q‐FP) in the assessment. Data sets from a prior CHB trial (NCT00962533) with mostly mild‐to‐moderate fibrosis participants were used for this study. 301 subjects with paired liver biopsies were consecutively included. Of these, 139 subjects were used to establish the test and the rest for internal validation. Fibrosis change between baseline and week 104 of treatment was blindly assessed with q‐FP and was compared with Ishak fibrosis staging. There were 70% and 93% subjects with Ishak F0‐2 at baseline and week 104, respectively. For the test of the subjects, q‐FP and Ishak staging showed no difference in determining the incidence of fibrosis regression (68% vs 67%; difference = 0.7%, P  = 1.00). Q‐FP demonstrated that the regression was independently associated with the antiviral efficacy endpoint (OR 3.0, 95% CI 1.4‐6.5, P  = .005), but Ishak failed the detection (OR 0.6, 95% CI 0.3‐1.3, P  = .24). Moreover, q‐FP directly revealed a higher fibrosis‐resistance to antiviral treatment in virus genotypes C vs B and in males vs females. These results were confirmed in the validation subjects. Additionally, a functional model built on the test subjects showed an accuracy of 82% in stratifying fibrosis reversibility of the validation subjects. In conclusion, q‐FP could have improved efficiency and accuracy in the longitudinal assessment of mild‐to‐moderate CHB fibrosis, indicating a potential alternative to current evaluation methodologies.